Mobilitätswende in Deutschland: E-Mobilität als Mittel der Wahl - Helena Wisbert (Wirtschaftsdienst, 2023)
– In contrast to other sectors, such as air traffic, the transition towards CO2-neutral mobility in the car sector is within reach, but thereis still a long way to go. Now the question arises: What role does e-mobility play in Germany today and in the future? The authors analyse theimportance of the model policy in the various market segments, the price development, and the framework conditions as levers for the ramp-upof e-mobility. The article further examines why synthetic fuels will not be able to play any significant role in the decarbonisation of the passengercar sector in the near future. Although the electric car has become mainstream, the conditions for a flourishing market must be created.
Keywords: H23; O25; R24; 330